PHYTOCHEMICAL SCREENING OF MANALAGI MANGO (Mangifera indica L.) LEAF INFUSE - Indarto; Kirwanto, Agus; Suhendriyo (Poltekkes Kemenkes Surakarta, 2024)
Mango is an incredibly popular fruit in Indonesia and plays a significant role in its agriculture. Among the many varieties of mango, the Manalagi (Mangifera indica L.) stands out for its remarkable taste and abundant size. Moreover, the leaves of this type of mango have been found to contain a medicinal property due to the presence of a compound called mangiferin. This compound is known to offer a wide range of benefits, including pain relief, antioxidant effects, anti-inflammatory effects, anti-diabetic properties, tumor-fighting abilities, and stamina-boosting effects. This study aimed to identify the presence of various phytochemical compounds, such as flavonoids, alkaloids, tannins, saponins, and steroids in Manalagi mango leaf infuse. The extraction was done using the infundation method and distilled water as the solvent. The qualitative phytochemical screening showed positive results on flavonoids, tannins, and steroid compounds.